2019
DOI: 10.11646/zootaxa.4592.1.1
|View full text |Cite
|
Sign up to set email alerts
|

An updated checklist of Canadian and Alaskan Collembola

Abstract: The available literature data on the species diversity and geographical distribution of Collembola in Canada and Alaska is summarized. In total, the checklist covers 541 named species of Collembola. This includes 475 species in 135 genera from 24 families recorded from Canada, as well as 241 species in 75 genera from 19 families reported from Alaska. For each species the current name, basionym with a full reference, records for different provinces and territories with their authorships, and general distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 490 publications
(17 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Terminology for the description follows that given in Fjellberg (1984, 1999), Babenko et al (1994) and Thibaud et al (2004).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Terminology for the description follows that given in Fjellberg (1984, 1999), Babenko et al (1994) and Thibaud et al (2004).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, subsequent studies (Fjellberg 1985, Babenko et al 1994, Babenko and Fjellberg 2006) showed that H. trybomi sensu Christiansen and Bellinger (1980) rather referred to H. oregonensis . Afterwards, Babenko et al (1994) supplemented the Christiansen and Bellinger (1980) definition with new essential features and enlarged the group by adding species recorded in Palearctic: H. maxillosa Babenko, 1994 and H. tethyca .…”
Section: Taxonomymentioning
confidence: 99%
See 3 more Smart Citations